MATHEMATICAL ARCHITECTURE OF MICROSERVICES FOR GEOGRAPHIC INFORMATION SYSTEM BASED HEALTH MANAGEMENT SYSTEM - Rai, Ankush; R, Jagadeesh Kannan (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Despite the wide adoption of distributed computing with several webs standards and cloud technologies; building of city wide health management system for smart city platform is a daunting task. Owing to the limitations in sparse learning of disease outbreak and its dynamic nature. As it would require development of a scalable, distributed and evolving architecture on the web; where a sparse machine learning based algorithm will enable authorities collaborate in preventing, controlling and responding to a specific disease outbreak and its time factor analysis. In this work, a mathematical system model is presented for sparse learning in Geographic Information System (GIS) based architecture to support continuity of microservices in health management setting. The model is able to continually cope with the transformation in architecture to match with the system goals of microservices and anticipate the evolutionary aspects of the architecture configuration.